THE IMPACT OF BRAND IMAGE AND PERCEIVED QUALITY ON CONSUMER PURCHASE DECISION OF SOMETHINC WITH KOREAN BRAND AMBASSADOR (NCT DREAM) AS MODERATING VARIABLE (Diponegoro Journal of Management, 2023)
ABSTRACT This study aims to explain: to determine the percentage of NCT Dream as a brand ambassador, whether it can influence the relationship between brand image and Perceived Quality on Purchasing decisions for the Somethinc brand. Research was conducted on Somethinc consumers who know that NCT Dream is an Somethinc brand ambassador. By distributing questionnaires to 140 respondents as a sample. The type of research used is quantitative research. sampling technique using purposive sampling. The analysis technique used is multiple regression analysis with the F test and T test. The results of the multiple regression analysis show that each variable, namely brand image and perceived quality, together has a significant effect on purchasing decisions. while the Korean Brand Ambassador Variable as a moderating variable succeeded in strengthening the relationship between Brand image to Consumer purchase Decisions and Perceived Quality to Consumer Purchase Decisions.